Protopine isolated from Nandina domestica induces apoptosis and autophagy in colon cancer cells by stabilizing p53. (1st April 2019) - Son, Younglim; An, Younju; Jung, Jaeyeon; Shin, Sora; Park, InWha; Gwak, Jungsug; Ju, Bong Gun; Chung, Young‐Hwa; Na, MinKyun; Oh, Sangtaek
Abstract : The tumor suppressor p53 plays essential roles in cellular protection mechanisms against a variety of stress stimuli and its activation induces apoptosis or autophagy in certain cancer cells. Here, we identified protopine, an isoquinoline alkaloid isolated from Nandina domestica, as an activator of the p53 pathway from cell‐based natural compound screening based on p53‐responsive transcription. Protopine increased the p53‐mediated transcriptional activity and promoted p53 phosphorylation at the Ser15 residue, resulting in stabilization of p53 protein. Moreover, protopine up‐regulated the expression of p21 WAF1/CIP1 and BAX, downstream genes of p53, and inhibited the proliferation of HCT116 colon cancer cells. Apoptosis was elicited by protopine as indicated by caspase‐3/7 activation, poly ADP ribose polymerase cleavage, and increased population of Annexin V‐FITC‐positive cells. Furthermore, protopine induced the formation of microtubule‐associated protein 1 light chain 3 (LC3) puncta and LC3‐II turnover, typical biochemical markers of autophagy, in HCT116 cells. Our findings suggest that protopine exerts its antiproliferative activity by stimulating the p53 pathway and may have potential as a chemopreventive agent for human colon cancer.